Wear Behavior Phenomena of TiN/TiAlN HiPIMS PVD-Coated Tools on Milling Inconel 718 - Vitor F. C. Sousa; Filipe Fernandes; Francisco J. G. Silva; Rúben D. F. S. Costa; Naiara Sebbe; Rita C. M. Sales-Contini (Metals, 2023)
Due to Inconel 718’s high mechanical properties, even at higher temperatures, tendency to work-harden, and low thermal conductivity, this alloy is considered hard to machine. The machining of this alloy causes high amounts of tool wear, leading to its premature failure. There seems to be a gap in the literature, particularly regarding milling and finishing operations applied to Inconel 718 parts. In the present study, the wear behavior of multilayered PVD HiPIMS (High-power impulse magnetron sputtering)-coated TiN/TiAlN end-mills used for finishing operations on Inconel 718 is evaluated, aiming to establish/expand the understanding of the wear behavior of coated tools when machining these alloys. Different machining parameters, such as cutting speed, cutting length, and feed per tooth, are tested, evaluating the influence of these parameters’ variations on tool wear. The sustained wear was evaluated using SEM (Scanning electron microscope) analysis, characterizing the tools’ wear and identifying the predominant wear mechanisms. The machined surface was also evaluated after each machining test, establishing a relationship between the tools’ wear and production quality. It was noticed that the feed rate parameter exerted the most influence on the tools’ production quality, while the cutting speed mostly impacted the tools’ wear. The main wear mechanisms identified were abrasion, material adhesion, cratering, and adhesive wear. The findings of this study might prove useful for future research conducted on this topic, either optimization studies or studies on the simulation of the milling of Inconel alloys, such as the one presented here.